2018
DOI: 10.1097/qad.0000000000002005
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in human papilloma virus types amongst United States women with HIV and cervical precancer

Abstract: Objective: Recent studies reported lower human papillomavirus 16 (HPV16) prevalence in cervical precancer among African American than Caucasian women in the general population. We assessed this relationship in women with HIV. Design: Women living with or at risk for HIV in the Women’s Interagency HIV Study were followed semi-annually with Pap tests, colposcopy/histology (if indicated), and collection of cervicovaginal lavage samples for HPV testing by PCR. Racial and ethnic groups were defined using genomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…This is consistent with results from earlier meta-analyses that have found women from SSA to have the lowest proportion globally of HPV16 in all grades of cervical lesions, regardless of HIV status (8,9,26,27). Meanwhile, U.S. studies have found lower HPV16 prevalence in CIN3þ in African American women compared with Caucasian women, regardless of HIV status and independent of immune status (28,29).…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with results from earlier meta-analyses that have found women from SSA to have the lowest proportion globally of HPV16 in all grades of cervical lesions, regardless of HIV status (8,9,26,27). Meanwhile, U.S. studies have found lower HPV16 prevalence in CIN3þ in African American women compared with Caucasian women, regardless of HIV status and independent of immune status (28,29).…”
Section: Discussionsupporting
confidence: 90%
“…Considering race, in the United States, the incidence of HIV+ women diagnosed with cervical intraepithelial neoplasia grade 3 or higher was higher in African-Americans than Caucasians, with a ratio of 5:1. In the United States, the prevalent strains of hrHPV among HIV+ African-American women diagnosed with cervical cancer were HPV-16 (26.8%), HPV-53 (20.5%), HPV-35 (15.2%) and HPV-52/58 (14.3%) [ 14 ]. There is a paucity of data on the relationship between the types of HPV observed in African-American women and African women.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have detected a significant percentage of non-16/18 hr-HPV genotypes, suggesting the presence of region-specific heterogeneity in the HPV genotype distribution [ 35 39 ]. Also, variation in HPV distribution among different ethnic groups has been reported in an American study [ 40 ]. Our finding has potential implication on Brunei’s national school-based HPV vaccination program [ 41 ] which currently provides vaccines which do not confer protection against non-16/18 genotypes.…”
Section: Discussionmentioning
confidence: 94%